1997
DOI: 10.1063/1.118693
|View full text |Cite
|
Sign up to set email alerts
|

Room-temperature photoluminescence and electroluminescence from Er-doped silicon-rich silicon oxide

Abstract: Correlation between the microstructure and electroluminescence properties of Er-doped metal-oxide semiconductor structures Appl. Phys. Lett. 94, 101916 (2009); 10.1063/1.3098474 Room-temperature 1.54 μm photoluminescence from Er-doped Si-rich silica layers obtained by reactive magnetron sputtering J. Appl. Phys. 94, 3869 (2003); 10.1063/1.1604479 Room-temperature 1.54 μm electroluminescence from Er-doped silicon-rich silicon oxide films deposited on n + -Si substrates by magnetron sputtering J. Appl. Phys. 90,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
21
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 14 publications
1
21
0
Order By: Relevance
“…Moreover, LEDs emitting in the infrared spectral range have also been already achieved based on Er 3þ emission. 7,11,12 Furthermore, promising results have also been obtained for SRSO doped with Nd 3þ ions with strong emission at around 1100 nm. 13 Recently, electroluminescence (EL) of Tb implanted silica thin films in MOS devices with external quantum efficiency as high as 10% 14,15 and EL from a Tb-doped SiN matrix have also been shown.…”
mentioning
confidence: 81%
“…Moreover, LEDs emitting in the infrared spectral range have also been already achieved based on Er 3þ emission. 7,11,12 Furthermore, promising results have also been obtained for SRSO doped with Nd 3þ ions with strong emission at around 1100 nm. 13 Recently, electroluminescence (EL) of Tb implanted silica thin films in MOS devices with external quantum efficiency as high as 10% 14,15 and EL from a Tb-doped SiN matrix have also been shown.…”
mentioning
confidence: 81%
“…Others have shown that SRSO films produced by oxidation of porous silicon doped electrochemically with erbium show room temperature Er 3ϩ luminescence. 13 Our results suggest that SRSO, by combining the advantages of SiO 2 and a-Si:H:O, may be a more efficient host material for Er than either one alone. We should note that it is likely that the large band gap of SRSO also contributes to the intense Er 3ϩ luminescence, as it was shown that a larger band gap of the host matrix tends to reduce the temperature quenching of the luminescence intensity.…”
mentioning
confidence: 91%
“…14 However, as the temperature quenching of Er 3ϩ luminescence from a-Si:H:O ͑Ref. 8͒ and from SRSO produced by oxidation of porous silicon 13 are about equal, the large band gap of SRSO alone cannot explain its greater Er 3ϩ luminescence intensity over a-Si:H:O. SRSO can also luminesce in the visible range if carriers can be confined effectively in the Si nanoclusters. 13 However, a sample without erbium did not show any visible luminescence, indicating that in this case the clusters were either too large or too close together for quantum confinement of carriers to be effective.…”
mentioning
confidence: 95%
“…In addition, the Er 3+ -related emission is very sensitive to interactions with the surrounding matrix. Silicon-rich silicon oxides [17,18] and porous silicon [19,20] have been shown to be very effective matrixes for Er doping at high concentrations, exhibiting intense infrared Er luminescence at room temperature. However, the concentration of optically active Er in such matrixes is typically limited to about 1 at% owing to concentration quenching and precipitation [21,22].…”
Section: Introductionmentioning
confidence: 99%